Sarcopenia in older mice is characterized by a decreased anabolic response to a protein meal. (March 2017) - van Dijk, Miriam; Nagel, Jolanda; Dijk, Francina J.; Salles, Jerôme; Verlaan, Sjors; Walrand, Stephane; van Norren, Klaske; Luiking, Yvette
Highlights: Compared to young mice (10 months), old mice (25 months) display significantly lower skeletal muscle mass, strength and function. Together with a decrease in physical activity and dietary protein intake, insulin sensitivity, and reduced anabolic response and indications of elevated oxidative stress. Evaluating sarcopenia in mice reveals strong translational value to human ageing. Abstract: Ageing is associated with sarcopenia, a progressive decline of skeletal muscle mass, muscle quality and muscle function. Reduced sensitivity of older muscles to respond to anabolic stimuli, i.e. anabolic resistance, is part of the underlying mechanisms. Although, muscle parameters have been studied in mice of various ages/strains; the aim was to study if mice display similar deteriorating processes as human ageing. Therefore, 10, 16, 21 and 25 months-old C57BL6/6J male mice were studied to measure parameters of sarcopenia and factors contributing to its pathophysiology, with the aim of characterizing sarcopenia in old mice. Muscle mass of the hind limb was lower in 25 as compared to 10 month-old mice. A significant decrease in physical daily activity, muscle grip strength and ex vivo muscle maximal force production was observed in 25 compared to 10 month-old mice. The muscle anabolic response to a single protein meal showed increased muscle protein synthesis in young, but not in old mice, indicative to anabolic resistance. However, by increasing the protein content in meals, anabolic resistance could be overcome, similar as in human elderly. Additionally, aged mice showed higher fasted insulin and hepatic malondialdehyde (MDA) levels (=marker oxidative stress). This study shows clear characteristics of sarcopenia that coincide with anabolic resistance, insulin resistance and oxidative stress in 25 month-old C57/BL6 male mice, similar to human ageing. Furthermore, similar decline in muscle mass, strength and function was observed in this aged-mice-model. These observations offer potential for the future to explore in old mice the effects of interventions targeting sarcopenia.